Compromised hepatic mitochondrial fatty acid oxidation and reduced markers of mitochondrial turnover in human NAFLD. Issue 5 (14th April 2022) - Moore, Mary P.; Cunningham, Rory P.; Meers, Grace M.; Johnson, Sarah A.; Wheeler, Andrew A.; Ganga, Rama R.; Spencer, Nicole M.; Pitt, James B.; Diaz‐Arias, Alberto; Swi, Ahmed I. A.; Hammoud, Ghassan M.; Ibdah, Jamal A.; et al.
Abstract: Background and Aims: NAFLD and its more‐advanced form, steatohepatitis (NASH), is associated with obesity and is an independent risk factor for cardiovascular, liver‐related, and all‐cause mortality. Available human data examining hepatic mitochondrial fatty acid oxidation (FAO) and hepatic mitochondrial turnover in NAFLD and NASH are scant. Approach and Results: To investigate this relationship, liver biopsies were obtained from patients with obesity undergoing bariatric surgery and data clustered into four groups based on hepatic histopathological classification: Control (CTRL; no disease); NAFL (steatosis only); Borderline‐NASH (steatosis with lobular inflammation or hepatocellular ballooning); and Definite‐NASH (D‐NASH; steatosis, lobular inflammation, and hepatocellular ballooning). Hepatic mitochondrial complete FAO to CO2 and the rate‐limiting enzyme in β‐oxidation (β‐hydroxyacyl‐CoA dehydrogenase activity) were reduced by 40%–50% with D‐NASH compared with CTRL. This corresponded with increased hepatic mitochondrial reactive oxygen species production, as well as dramatic reductions in markers of mitochondrial biogenesis, autophagy, mitophagy, fission, and fusion in NAFL and NASH. Conclusions: These findings suggest that compromised hepatic FAO and mitochondrial turnover are intimately linked to increasing NAFLD severity in patients with obesity.